2007
DOI: 10.1111/j.1750-3639.2007.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Distribution of West Nile Virus Infection: Postmortem Immunohistochemical Study of Six Cases

Abstract: Rare cases of West Nile virus (WNV)-associated inflammation outside the central nervous system (CNS) have been reported. We evaluated the systemic distribution of WNV in postmortem tissues during encephalitis in six patients using immunohistochemistry. WNV antigens were detected in neurons of CNS (all 6 cases), kidney (4 cases), lungs (2 cases), pancreas (2 cases), thyroid (2 cases), intestine (2 cases), stomach (1 case), esophagus (1 case), bile duct (1 case), skin (1 case), prostate (1 case) and testis (1 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 62 publications
7
79
0
Order By: Relevance
“…At that time, animals show a fairly widespread infection, including infection of most neurons except for cerebellar granular neurons (data not shown). There is a broad distribution of other infected organs, similar to that reported in autopsies of infected immunosuppressed humans (4). Immunofluorescent staining of kidney sections using antibodies to WNV demonstrate occasional infected renal tubules (Fig.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…At that time, animals show a fairly widespread infection, including infection of most neurons except for cerebellar granular neurons (data not shown). There is a broad distribution of other infected organs, similar to that reported in autopsies of infected immunosuppressed humans (4). Immunofluorescent staining of kidney sections using antibodies to WNV demonstrate occasional infected renal tubules (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Analyses of tissues obtained from WNV-infected humans, hamsters, or mice have revealed that epithelial cells are important targets of viral infection (4,20,51) in such organs as the kidney, intestine, testes, and bile duct. In these tissues, epithelial cells form TJ, resulting in barrier formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases, religious and cultural concerns have greatly restricted access to tissue samples from cadavers. Moreover, the distribution of virus and histopathological changes in the brain vary markedly depending on the time taken for different individuals to succumb to infection [104] and their immune status [6]. Additionally, post-mortem human specimens only provide a snapshot of pathological markers and virus distribution in the terminal phase of disease.…”
Section: The Application Of Mice To Model Flavivirus Encephalitismentioning
confidence: 99%